ANALISA TERHADAP TANAH ULAYAT YANG DIBEBANI HAK GUNA USAHA (HGU) - Melia Rizki Ruswandi (Yurisprudentia: Jurnal Hukum Ekonomi, 2025)
The state respects and recognizes the existence of indigenous peoples. Indigenous peoples are also given rights by the state, including rights to customary or communal land for the survival of indigenous peoples. The state protects all interests of indigenous peoples by establishing Law No. 5 of 1960 concerning Agrarian Affairs. In this article, the author will discuss the problems that arise in society about whether customary rights can be burdened with HGU and what legal impacts arise if the customary land rights of indigenous peoples have been burdened with HGU. So the answer is, first, if the land in question is customary land, it cannot be mortgaged to any party because customary land is not owned individually. Second, although customary rights are communalistic religious. This means that it is possible to control customary land individually, but the use of customary rights is carried out by acting as members of a customary law group, both territorial and genealogical. The nature of control owned by customary land rights contains an element of togetherness, but in its implementation, the granting of HGU on customary land has occurred a lot among indigenous communities. One example of a case that the author raised was HGU on customary land in West Pasaman. The legal consequences arising from the lack of synchronization and harmonization between government regulations and permits granted with applicable customary law have created several problems that arise in society or conflicts between companies holding HGU permits and indigenous communities regarding the status of customary land, confiscation by banks if there is a default on mortgage rights, and land status if the HGU period has ended. Therefore, this article is expected to answer the confusion about the status of customary rights burdened with HGU and answer the legal issues that arise.